County Fairs in the ‘USA’: Overview from the COVID 19 Pandemic Era - caliskan, vedat (Turizam, 2023)
Fairs, which have been seen in several forms in various parts of the world throughout history, represent one of the oldest and most colorful events in the world. Today, the USA comes first among the countries with the highest number of fairs. County fairs, the early examples of which were seen in the 18th century in the USA, became widespread throughout the country with the agricultural-society movement. Combining traditions of agricultural education and exhibition with amusement and community traditions, county fairs are widely distributed in the United States and still attract great attention.This study aims to determine the current existence state and geographical and seasonal distribution of US county fairs, for this purpose a questionnaire was developed for fair boards administrations to respond. In addition to the main physical, functional and administrative features of the fairs, the effects of the COVID 19 pandemic, which deeply affects the fair organizations, are among the topics discussed in the research. The findings reveal that county fairs, which can be seen in almost every state, are especially geographically concentrated on states in the Midwest region, and are mostly held in summer and August. Although the COVID 19 pandemic period has led to the cancellation of many fairs, fair board representatives have optimistic expectations that the interest will increase after the pandemic period.